Psychosocial factors and hypertension prevalence among Ghanaians in Ghana and Ghanaian migrants in Europe: The RODAM study. Issue 2 (November 2019) - Awuah, Raphael Baffour; de-Graft Aikins, Ama; Dodoo, F Nii-Amoo; Meeks, Karlijn AC; Beune, Eric JAJ; Klipstein-Grobusch, Kerstin; Addo, Juliet; Smeeth, Liam; Bahendeka, Silver K; Agyemang, Charles
Despite progress made to prevent and control hypertension, its prevalence has persisted in many countries. This study examined the associations between psychosocial factors and hypertension among Ghanaian non-migrants and migrants. Data were drawn from the Research on Obesity and Diabetes among African Migrants (RODAM) project. Findings show that among migrant women, those who experienced periods of stress at home/work had higher odds of hypertension. Among non-migrants, women with depression symptoms were more likely to be hypertensive. Furthermore, there was a positive association between negative life events and hypertension among non-migrant men. The findings highlight the importance of psychosocial factors in addressing hypertension prevalence in Ghanaian populations.